KatG Is the Primary Detoxifier of Hydrogen Peroxide Produced by Aerobic Metabolism in Bradyrhizobium japonicum - Panek, Heather R. (American Society for Microbiology, 2004)
Bacteria are exposed to reactive oxygen species from the environment and from those generated by aerobic metabolism. Catalases are heme proteins that detoxify H(2)O(2), and many bacteria contain more than one catalase enzyme. Also, the nonheme peroxidase alkyl hydroperoxide reductase (Ahp) is the major scavenger of endogenous H(2)O(2) in Escherichia coli. Here, we show that aerobically grown Bradyrhizobium japonicum cells express a single catalase activity. Four genes encoding putative catalases in the B. japonicum genome were identified, including a katG homolog encoding a catalase-peroxidase. Deletion of the katG gene resulted in loss of catalase activity in cell extracts and of exogenous H(2)O(2) consumption by whole cells. The katG strain had a severe aerobic growth phenotype but showed improved growth in the absence of O(2). By contrast, a B. japonicum ahpCD mutant grew well aerobically and consumed H(2)O(2) at wild-type rates. A heme-deficient hemA mutant expressed about one-third of the KatG activity as the wild type but grew well aerobically and scavenged low concentrations of exogenous H(2)O(2). However, cells of the hemA strain were deficient in consumption of high concentrations of H(2)O(2) and were very sensitive to killing by short exposure to H(2)O(2). In addition, KatG activity did not decrease as a result of mutation of the gene encoding the transcriptional activator OxyR. We conclude that aerobic metabolism produces toxic levels of H(2)O(2) in B. japonicum, which is detoxified primarily by KatG. Furthermore, the katG level sufficient for detoxification does not require OxyR.